2017
DOI: 10.1155/2017/4208178
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Outcomes of Patients with Multifocal Papillary Thyroid Microcarcinomas and Larger Tumors

Abstract: A retrospective review of 626 patients with multifocal papillary thyroid carcinoma (PTC) including 147 patients (23.5%) with multifocal papillary thyroid microcarcinoma (PTMC) from a total of 2,536 patients with PTC who visited the Chang Gung Medical Center in Linkou, Taiwan, was performed. A comparison of the clinical features between 626 multifocal and 1,910 solitary PTC cases showed that patients in the multifocal PTC group were older and had a smaller mean tumor size, a more advanced tumor-node-metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
1
15
2
2
Order By: Relevance
“…PTCs often arise as multiple tumor foci, which are considered the result of multiple synchronous primary tumors arising from independent clones. The incidence of multifocal PTMCs has been reported as 23.5-36.1% [11][12][13]. In our study, multiple PTMCs were detected in 29.81% (31/104) of cases, which was higher than the corresponding percentage in the MTMC group.…”
Section: Discussioncontrasting
confidence: 44%
“…PTCs often arise as multiple tumor foci, which are considered the result of multiple synchronous primary tumors arising from independent clones. The incidence of multifocal PTMCs has been reported as 23.5-36.1% [11][12][13]. In our study, multiple PTMCs were detected in 29.81% (31/104) of cases, which was higher than the corresponding percentage in the MTMC group.…”
Section: Discussioncontrasting
confidence: 44%
“…PTCs often arise as multiple tumor foci, which are considered as the result of multiple synchronous primary tumors arising from independent clones. The incidence of multifocal PTMCs has been reported as 23.5%-36.1% [11][12][13]. In our study, multiple PTMCs was detected in 29.81% (31/104) cases, which was higher than that in MTMCs group.…”
Section: Discussionsupporting
confidence: 38%
“…Multifocality and bilaterality are common features in PTMC and are considered risk factors for disease recurrence. [4,5] According to the observations from Lu et al, [6] multifocality may arise from intrathyroidal metastases from a single cancer cell clone or from multiple independent origins. This latter hypothesis was investigated by some modern molecular techniques, which confirmed that PTMCs are multiple synchronous primary tumors arising from autonomic clones.…”
Section: Introductionmentioning
confidence: 99%